A REVIEW ON A ROBUST DIGITAL IMAGE WATERMARKING USING DWT-PCA - Ganesh N. Shinde (International Journal of Innovations in Engineering Research and Technology, 2022)
A complete approach for watermarking is presented in this System, by using Discrete Wavelet Transform (DWT) and Principal Component Analysis (PCA). There are some watermarking techniques like DCT, DWT, and DWT-SVD, but there is a disadvantage in the watermarking to withstand attacks. Hence the new digital image watermarking algorithm is proposed which provide robust watermarking with minimal amount of distortion in case of attacks. DWT offers scalability and PCA helps in diminishing relationship among the wavelet coefficients acquired from wavelet disintegration of each square in this manner scattering the watermark bits into the interrelated coefficient. Peak signal-tonoise ratio (PSNR) is used as a measure for invisibility in watermarked image. The higher value of PSNR indicates the better invisibility of watermark. whereas similarity between two images by normalized correlation coefficient test the transparency and robustness against various attacks like cropping, noise, rotation, filtering etc. The proposed system should provide the recoverable watermark without any reasonable amount of distortion even in case of attacks.